[Diatomite Plant at Namasfjord] - Streng, Evelyn Fiedler (1975)
Photograph of a diatomite plant at Namasfjord. White, rectangular buildings sit along the brown, flat ground in the foreground. A stack of brown pallets sits outside a building to the left. Cars are parked outside the buildings to the right. Tall, white fumes shoot out from the background into the clouded sky. Rounded, brown mountains are visible in the distance.